(untitled) - Vaes, Stefaan (Comptes Rendus. Mathématique)
We construct an exotic example of a locally compact group $\mathcal{G}$ with a Borel $2$-cocycle $ω $ such that the non-twisted group von Neumann algebra $L(\mathcal{G})$ is a factor, while the twisted group von Neumann algebra $L_ω (\mathcal{G})$ has a diffuse center.